Financial Performance of Islamic Banks in Turkey and the United Kingdom: A Comparative Study - Ondes, Turan; Ahmid, Almabrok F.; Faraj, Abdullah (European Scientific Journal, ESJ, 2019)
Islamic banks are financial institutions just like conventional banks. However, Islamic banks do not deal with interest and are based on participation. These institutions raise funds and employ them within the scope of Islamic (Shariah) principles where the bank and the depositor share the business, thus sharing the profits and losses. This paper focuses on making a comparative between three Islamic banks in Turkey and five Islamic banks in the United Kingdom in terms of financial performance. More so, it aims to investigate whether or not Islamic banks in Turkey are more profitable, less risky, liquid, operationally efficient, and have a good management quality compared to the Islamic banks in UK. The time span used in this study is one period. The period is four years from 2013 until 2016. Our study used time series data (pooled Least Squares) (PLS) as panel regression on nine financial ratios (CAMEL) to examine the financial performance of these banks according to their profitability, Capital adequacy, Asset quality (riskiness and solvency), Management quality, Earning diversification (operationally efficient), and Liquidity. However, our results are insignificant for UK and significant in Turkey in terms of asset quality and management quality.